A survey of χ‐boundedness. Issue 3 (24th August 2020) - Scott, Alex; Seymour, Paul
Abstract: If a graph has bounded clique number and sufficiently large chromatic number, what can we say about its induced subgraphs? András Gyárfás made a number of challenging conjectures about this in the early 1980s, which have remained open until recently; but in the last few years there has been substantial progress. This is a survey of where we are now.